Fasting as a Trigger of Migraine: Epidemiology, Pathophysiological Mechanisms, and Clinical Approach - a Narrative Review - Tokarczyk, Michał; Samujlik, Andrzej; Karczewska, Kinga; Kurowska, Małgorzata; Ziółek, Małgorzata Anna; Kuniewicz, Jagoda; Kuczkowska, Julia Maria; Skorupa, Maria Karolina; Wątek, Milena; Piszczek, Tomasz (Quality in Sport, 2026)
Background. Migraine is a complex neurobiological disorder and one of the leading causes of disability worldwide, affecting approximately 14.1% of the global population. Among the numerous factors capable of precipitating migraine attacks, fasting occupies a particularly prominent position, yet the underlying mechanisms and clinical implications of this relationship remain incompletely understood. Aim. To synthesize current evidence regarding fasting as a migraine trigger, with particular emphasis on its epidemiology, proposed pathophysiological mechanisms, and clinical approach. Material and methods. A narrative literature review was conducted using PubMed and Google Scholar. Original articles, reviews, case series, and case reports were analyzed. The studies included both clinical human studies and experimental animal models. Results. Fasting is reported as a migraine trigger by approximately 44% of patients, making it one of the most prevalent dietary precipitants. Multiple pathophysiological mechanisms have been proposed, including hypoglycemia-driven modulation of cortical spreading depression, astrocytic glycogen depletion, hypothalamic orexinergic and neuropeptide Y pathway dysregulation, and caffeine withdrawal. Clinical data further reveal persistent gaps between trigger recognition and behavioral modification among patients, while short-term preventive pharmacotherapy with rimegepant during predictable fasting periods has been examined in migraine populations. Conclusions. Fasting represents a prevalent, modifiable, and mechanistically plausible migraine trigger acting through multiple converging pathways. Its systematic identification during clinical assessment, combined with individualized lifestyle and pharmacological strategies, may contribute to reducing attack burden in susceptible individuals. Further prospective research and randomized trials are needed to establish evidence-based recommendations.